2019
DOI: 10.1177/0363546519869671
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Revision Hip Arthroscopic Surgery: A Systematic Review and Meta-analysis

Abstract: Background: While the indications for primary hip arthroscopic surgery in treating femoroacetabular abnormalities continue to be defined, the indications and outcomes for revision hip arthroscopic surgery remain ambiguous. However, revision hip arthroscopic surgery is performed in 5% to 14% of patients after their index procedure. While patient-reported outcomes (PROs) generally improve after revision procedures, the extent of their improvement is not well defined. Purpose: To determine the outcomes and effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…Additionally, at final follow-up, the average mHHS in our cohort was 76.8, which is similar to the value of 74.61 reported in the results of a meta-analysis on RHA by O’Connor et al. 21 Of note, our cohort’s average NAHS at final follow-up was 80.1, within the range of values reported in the literature on RHA (69.00-83.70). 22 , 23 These results suggest that RHA generally has positive implications for patients.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, at final follow-up, the average mHHS in our cohort was 76.8, which is similar to the value of 74.61 reported in the results of a meta-analysis on RHA by O’Connor et al. 21 Of note, our cohort’s average NAHS at final follow-up was 80.1, within the range of values reported in the literature on RHA (69.00-83.70). 22 , 23 These results suggest that RHA generally has positive implications for patients.…”
Section: Discussionsupporting
confidence: 89%
“…Only 2 patients in our failure cohort (25%) had failure because they underwent revision procedures. O'Connor et al 21 recently reported in a meta-analysis that RHA does indeed result in significant improvements in PROMs but still less than those for primary hip arthroscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies do show significant improvement in patient-reported outcome (PRO) following revision hip arthroscopy ( 34 , 36 ). A meta-analysis by O'Connor et al ( 37 ) reported a significant improvement in all PRO scores from before operation to the latest follow-up after revision, with the greatest average increase shown in the modified Harris Hip Score (mHHS) (+17.20) and the Hip Outcome Score–Activities of Daily Living (HOS-ADL) (+13.98), and a decrease in the visual analog scale for pain (VAS) (−3.16). Domb et al ( 34 ) reported similar results from a study of 47 revision hip arthroscopies at a mean length of follow-up of 29 months, concluding a statistically significant improvement in each PRO measured: mHHS, HOS-ADL, HOS Sports Subscale (HOS-SS), VAS for pain, and the Non-arthritic Hip Score (NAHS).…”
Section: Discussionmentioning
confidence: 99%
“…T he arthroscopic management of focal chondral lesions of the hip has evolved in an attempt to alleviate symptoms and mitigate progressive chondrolabral damage while treating femoroacetabular impingement syndrome (FAIS). [1][2][3] This evolution has included abrasion chondroplasty, 4 microfracture, 5 fibrin adhesive for partly detached acetabular cartilage flaps, 6 mononuclear cell concentrate with platelet-rich plasma, 7 various types of autologous cartilage grafts, [8][9][10][11][12][13] and synthetic matrix substances, 14,15 among other hip preservation techniques. In earlier reports, the underlying surgical principles consistently aimed at debriding the loose cartilage fragments from the defect bed and creating stable margins.…”
mentioning
confidence: 99%